A comparison of two non-thrust mobilization techniques applied to the C7 segment in patients with restricted and painful cervical rotation. (November 2014) - Creighton, Doug; Gruca, Mark; Marsh, Douglas; Murphy, Nancy
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Cervical mobilization and manipulation have been shown to improve cervical range of motion and pain. Rotatory thrust manipulation applied to the lower cervical segments is associated with controversy and the potential for eliciting adverse reactions (AR). The purpose of this clinical trial was to describe two translatory non-thrust mobilization techniques and evaluate their effect on cervical pain, motion restriction, and whether any adverse effects were reported when applied to the C7 segment. Methods: This trial included 30 participants with painful and restricted cervical rotation. Participants were randomly assigned to receive one of the two mobilization techniques. Active cervical rotation and pain intensity measurements were recorded pre- and post-intervention. Within group comparisons were determined using the Wilcoxon signed-rank test and between group comparisons were analyzed using the Mann–Whitney U test. Significance was set at P = 0·05. Results: Thirty participants were evaluated immediately after one of the two mobilization techniques was applied. There was a statistically significant difference (improvement) for active cervical rotation after application of the C7 facet distraction technique for both right (P = 0·022) and left (P = 0·022) rotation. Statistically significant improvement was also found for the C7 facet gliding technique for both right (P = 0·022) and left rotation (P = 0·020). Pain reduction was statistically significant for both right and left rotation after application of both techniques. Both mobilization techniques produced similar positive effects and one was not statistically superior to the other. Discussion: A single application of both C7 mobilization techniques improved active cervical rotation, reduced perceived pain, and did not produce any AR in 30 patients with neck pain and movement limitation. These two non-thrust techniques may offer clinicians an additional safe and effective manual intervention for patients with limited and painful cervical rotation. A more robust experimental design is recommended to further examine these and similar cervical translatory mobilization techniques.